Relationship between short-term memory impairment and the dorsolateral prefrontal cortex injury in patients with mild traumatic brain injury - Min Jye Cho; Han Do Lee; Jae Woon Kim; Sung Ho Jang (Journal of Integrative Neuroscience, 2022)
Background: The prefrontal cortex (PFC) has been reported to be related to memory function. Especially, the dorsolateral PFC (DLPFC) is a substantial neural structure in short-term memory. In this study, using diffusion tensor tractography (DTT), we investigated the relationship between short-term memory impairment and the DLPFC injury in patients with mild traumatic brain injury (TBI). Methods: We recruited 46 consecutive chronic patients with mild TBI and 42 normal control subjects. Fractional anisotropy (FA) and fiber number (FN) of the prefronto-thalamic tracts were determined for both hemispheres. Results: Significant differences were detected in the FA value of the DLPFC and FN value of the prefronto-thalamic tracts in the patient and control groups (p < 0.05). However, no significant differences were detected in the ventrolateral PFC (VLPFC) and orbitofrontal cortex (OFC) between the patient and control groups (p > 0.05). In addition, the FN value of the DLPFC showed moderate positive correlation with short-term memory (r = 0.510, p < 0.05). However, no significant correlations were detected between the short-term memory and the FA value of the DLPFC, and the FA and FN values of the VLPFC and OFC in the patient group (p > 0.05). Conclusions: We found that the short-term memory impairment was closely associated with the DLPFC injury in patients with mild TBI. Our results suggest that the estimation of the DLPFC using DTT would be useful for patients with severity of short-term memory impairment following mild TBI.